POTENSI BAHAN CETAK EKSTRAK NATRIUM ALGINAT RUMPUT LAUT MERAH (Kappaphycus alvarezii) DALAM MENGHAMBAT PERTUMBUHAN Streptococcus mutans - Inneke Dwi Lestari; Depi Praharani; Achmad Gunadi; Izzata Barid; Didin Erma Indahyani; Niken Probosari (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: Synthetic alginate is an impression material that is widely used in dentistry. Dental impressions may carry Streptococcus mutans bacteria, which is cariogenic bacteria. Red seaweed has the potential as a source of sodium alginate and has antibacterial activity. Aim: The purpose of this study is to analyze the ability of impression materials containing sodium alginate from red seaweed in inhibiting the growth of S. mutans bacteria. Methods: This study uses a laboratory experimental method with a post-test-only control group design. The number of research samples is 24, which are divided into group A (control), group B (red seaweed sodium alginate extract), and group C (red seaweed sodium alginate extract impression material). Sodium alginate was extracted from red seaweed (Kappaphycus alvarezii) by the acid method. Inhibition test of the growth of S. mutans bacteria using well diffusion method. Growth inhibition is characterized by the formation of an inhibition zone. Result: The test results showed that group A (control) does not have the ability to inhibit the growth of S. mutans bacteria. Meanwhile, group B (RLM Na- alginate extract) and group C (RLM Na-alginate extract impression material) have the same ability to inhibit the growth of S. mutans bacteria. Conclusions: Red seaweed sodium alginate extract impression material can inhibit the growth of S. mutans